MAXIMUM POWER POINT IN ORGANIC PHOTOVOLTAIC CELLS BY USING RTO OPTIMIZATION ALGORITHM. - RACHid, LABSI; LAHCENE, LAICHE (University Of El Oued, 2019)
"Nowadays, a lot of research work has been done to improve the use of sun energy, the most prominent of which is researched the photovoltaic cells to produce electricity. The generation of electricity using photovoltaic solar cells has been one of the most researched and studied subjects. Photovoltaic is the technology that uses solar cells. A solar cell is an electronic device which directly converts sunlight into electricity. Light shining on the solar cell produces both a current and a voltage to generate electric power. This process requires firstly, a material in which the absorption of light raises an electron to a higher energy state, and secondly, the movement of this higher energy electron from the solar cell into an external circuit. The electron then dissipates its energy in the external circuit and returns to the solar cell. A variety of materials and processes can potentially satisfy the requirements for photovoltaic energy conversion, but in practice nearly all photovoltaic energy conversion uses semiconductor materials in the form of a p-n junction. Because in the recent technology of PV cells has a very high cost, a new nanotechnology being inexpensive to fabricate, lightweight, and mechanically flexible, this revolutionary technology for electrical energy production called: Organic Photovoltaic cells (OPV) which is selected to do a study it in this work. The Photovoltaic voltage-current (V-I) characteristic is nonlinear and changes with irradiation and temperature. In general, there is a point on the V-I or voltage-power (V-P) curves, called the Maximum power point (MPP), at which PV operates with maximum efficiency and produces its maximum output power. The state of the art techniques to track the maximum available output power of PV systems are called the maximum-power point tracking (MPPT). The issue of maximum power point tracking (MPPT) has been addressed in different ways in the literature: examples of fuzzy logic, neural networks, DSP and Perturb and Observe (P&O) based implementations. Nevertheless, the Root Tree Optimization (RTO) technique is the best one used from its efficiency and robustness. In this thesis, we have used the Root Tree Optimization (RTO) algorithm to search the Optimal value of maximum power point (MPPopt), for Organic Photovoltaic cells (OPV) and compare the obtained results to another method called Perturb and Observe (P&O), and this is done for a given temperature and irradiance, to improve the utilization of the produced energy when connected to a load. Keywords: Optimal value of maximum power point (MPPopt), Root Tree Optimization (RTO), Perturb and Observe (P&O), Organic Photovoltaic cells (OPV), Photovoltaic voltage-current (V-I) characteristic. " "في الوقت الحاضر، تم القيام بالكثير من العمل البحثي لتحسين استخدام طاقة الشمس، ومن أبرزها البحوث المتعلقة بالخلايا الضوئية لإنتاج الكهرباء. لقد كان توليد الكهرباء باستخدام الخلايا الشمسية الضوئية واحداً من أكثر المواضيع بحثا ودراسة. الكهروضوئية هي التكنولوجيا التي تستخدم الخلايا الشمسية ، وهي عبارة عن جهاز إلكتروني يحول أشعة الشمس مباشرة إلى كهرباء. ينتج الضوء الساطع على الخلية الشمسية كلاً من التيار الكهربائي والجهد لتوليد الطاقة الكهربائية.و تتطلب هذه العملية أولاً ، مادة يرفع فيها امتصاص الضوء إلكترونًا إلى حالة طاقة أعلى ، وثانيًا ، حركة إلكترون الطاقة العالي هذا من الخلية الشمسية إلى دارة خارجية. ثم يقوم الإلكترون بتبديد طاقته في الدائرة الخارجية ويعود إلى الخلية الشمسية. يمكن أن تفي مجموعة متنوعة من المواد والعمليات بمتطلبات تحويل الطاقة الكهروضوئية ، ولكن في الممارسة العملية ، يستخدم كل تحويل الطاقة الكهروضوئية تقريبًا مواد أشباه الموصلات في شكل p-n junction. ولأن التكنولوجيا الحديثة للخلايا الكهروضوئية لديها تكلفة عالية جدا ، وتكنولوجيا النانو الجديدة كونها غير مكلفة للتصنيع ، وخفيفة الوزن ، ومرنة ميكانيكيا ، هذه التكنولوجيا الثورية لإنتاج الطاقة الكهربائية تسمى: الخلايا الضوئية العضوية (OPV) والتي تم اختيارها هنا للقيام بدراستها في هذا العمل. ان خاصية الجهد الكهروضوئي الحالية (V-I) غير خطية وتتغير مع الإشعاع ودرجة الحرارة. بشكل عام ، هناك نقطة على منحنيات V-I أو الجهد الكهربي (V-P) ، تسمى نقطة الطاقة القصوى (MPP) ، حيث تعمل PV بأقصى قدر من الكفاءة وتنتج أقصى طاقة خرج. يطلق على أحدث التقنيات لتعقب أقصى طاقة إنتاج متوفرة للأنظمة الكهروضوئية تتبع نقطة القدرة القصوى (MPPT). لفد تمت معالجة مسألة تتبع نقطة القدرة القصوى (MPPT) بطرق مختلفة في الأطروحات: أمثلة على ذلك: المنطق الغامض والشبكات العصبية والتطبيقات القائمة على DSP و خوارزمية اضطراب ومراقبة (P&O). ومع ذلك ، فإن تقنية جذور الشجر المثالیة (RTO) هي أفضل التقنيات المستخدمة من حيث كفاءتها وقوتها. في هذه الرسالة ، استخدمنا خوارزمية جذور الشجر المثالیة (RTO) للبحث في القيمة المثلى لنقطة الطاقة القصوى (MPPopt) ، للخلايا الضوئية العضوية (OPV) ومقارنة النتائج التي تم الحصول عليها بطريقة أخرى تسمى: خوارزمية اضطراب ومراقبة (P&O) ، ويتم ذلك بالحصول على درجة حرارة معينة والإشعاع ، لتحسين استخدام الطاقة المنتجة عند توصيله مع الحمل. الكلمات المفتاحية: القيمة المثلى لنقطة الطاقة القصوى (MPPopt) ، خوارزمیة جذور الشجر المثالیة (RTO) ، خوارزمية اضطراب ومراقبة (P&O)، الخلايا الضوئية العضوية (OPV) ، خاصية الجهد الكهروضوئي (V-I). "
Electromécanique مذكرة ماستر تخصص
Keywords: "Optimal value of maximum power point (MPPopt), Root Tree Optimization (RTO), Perturb and Observe (P&O), Organic Photovoltaic cells (OPV), Photovoltaic voltage-current (V-I) characteristic. "; القيمة المثلى لنقطة الطاقة القصوى (MPPopt) ، خوارزمیة جذور الشجر المثالیة (RTO) ، خوارزمية اضطراب ومراقبة (P&O)، الخلايا الضوئية العضوية (OPV) ، خاصية الجهد الكهروضوئي (V-I).